Horror Movies in the Teaching of Philosophy - Porras Navarro, Daniel (2018)
With this paper, we intend to resignify the use of non-traditional film productions in education (specifically, horror films) as a means of pedagogical transposition. This is intended to generate an interest that leads to the generation of knowledge by students from something as ordinary as watching a movie. In turn, bringing cinema to classes (specifically a cinema as unexpected and transgressive as horror), could promote the redefinition of space, of the academic, of Philosophy itself and even of everyday life.